PEDAGOGY FOR ADULTS: CONCEPT AND EPISTEMOLOGY - USM ADMIN (Moldova State University, 2021)
This article addresses the issue of establishing and developing adult pedagogy from the perspective of epistemology: to establish the factual categories and guidelines of adult pedagogy. The psychological and philosophical-pedagogical approaches to adult learning and education and the connection of adult pedagogy with other sciences are extensively analysed. The concept produced contributes to the elaboration of a Reference Framework of adult education in formal, non-formal and informal plan. Keywords: adult pedagogy, adult learning and education, andragogy, epistemology, psychological concepts, philoso- phical-pedagogical models, formal education, non-formal education, informal education.